Concentration risk and internal rate of return: Evidence from the infrastructure equity market. Issue 3 (April 2017) - Santandrea, Martina; Sironi, Andrea; Grassi, Laura; Giorgino, Marco
Abstract: Although an adequate risk sharing is considered essential for the value for money of Private Finance Initiatives (PFIs), research has not yet considered if the market concentration of equity holders influences the return of projects in which they invest. Basing on a comprehensive dataset of 706 UK PFIs, our analysis suggests that the equity market concentration influences the return on projects and, therefore, the price paid by the public sector to remunerate its private partners. Furthermore, the return on PFIs is correlated to the power exercised by the central lobby investors, mainly financial ones. Since the recent evolution of the PFI policy requires a greater involvement of equity holders, policymakers should take into consideration the market concentration risk that can significantly impact on the value for money of such projects.